Introduction: Issues affecting the regulatory environment for organic food safety in asia pacific - Bee Chen Goh (2020)
© Springer Nature Singapore Pte Ltd. 2020. As organic production and consumption continue to be on the rise globally, and specifically in the Asia Pacific region for the purpose of this book, the regulatory environment for organics has become all the more relevant and significant. Concerns for food safety, animal welfare, and climate emergency propel a drive for organics worldwide. Yet, as contributors of this edited volume have observed, there is no consistency across jurisdictions in the Asia Pacific for the regulation of organics. For instance, the regulatory framework that exists for organic certification, and for organic labelling, may be mandatory or voluntary. International trade, whether bilateral or multilateral, can be enhanced by way of regulatory harmonization or through mutual recognition regimes in organics. Historical accounts leading to an organic regulatory regime for organic agriculture and organic food products have also demonstrated the challenging issues involved in complying with standards and market distribution. It is hoped that this book will make a major contribution to the reader’s understanding of the regulatory issues involved in organic food safety in the Asia Pacific.